2023
DOI: 10.1038/s41467-023-37003-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in planta production of amidated antimicrobial peptides that are active against drug-resistant ESKAPE pathogens

Abstract: Antimicrobial peptides (AMPs) are promising next-generation antibiotics that can be used to combat drug-resistant pathogens. However, the high cost involved in AMP synthesis and their short plasma half-life render their clinical translation a challenge. To address these shortcomings, we report efficient production of bioactive amidated AMPs by transient expression of glycine-extended AMPs in Nicotiana benthamiana line expressing the mammalian enzyme peptidylglycine α-amidating mono-oxygenase (PAM). Cationic AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The widespread use and even abuse of antibiotics have rapidly increased bacterial resistance. , Especially six superbugs, ESKAPE (Escherichia coli, Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter), have been identified that pose a substantial threat to public health owing to their ability to increase the mortality rate. , Hence, developing new broad-spectrum antibacterial agents with unique structures that can protect against the ESKAPE strains is essential to mitigate the global drug resistance problem, which has emerged because new structural molecules may act on the unconventional antibacterial mechanisms. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use and even abuse of antibiotics have rapidly increased bacterial resistance. , Especially six superbugs, ESKAPE (Escherichia coli, Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter), have been identified that pose a substantial threat to public health owing to their ability to increase the mortality rate. , Hence, developing new broad-spectrum antibacterial agents with unique structures that can protect against the ESKAPE strains is essential to mitigate the global drug resistance problem, which has emerged because new structural molecules may act on the unconventional antibacterial mechanisms. , …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Especially six superbugs, ESKAPE (Escherichia coli, Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter), have been identified that pose a substantial threat to public health owing to their ability to increase the mortality rate. 3,4 Hence, developing new broad-spectrum antibacterial agents with unique structures that can protect against the ESKAPE strains is essential to mitigate the global drug resistance problem, which has emerged because new structural molecules may act on the unconventional antibacterial mechanisms. 5,6 Since the second half of the last century, the focus of the global market has transferred from cephalosporin to chemosynthetic quinolones, which exhibit a broad-spectrum antibacterial activity and outstanding curative effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yeni AMP bazlı ilaçların geliştirilmesi, biyoteknolojik çalışmalar ve farmasötik değerlendirme için bu moleküllerin büyük miktarlarda elde edilmesini gerektirir (Roshanak vd., 2023). Son birkaç yılda, birkaç yeni teknoloji nedeniyle AMP'lerin endüstriyel ölçekte üretilmesinde dikkate değer gelişmeler olmuştur (Chaudhary vd., 2023). AMP'lerin birçok faydalı özelliğine rağmen uygulama sonrasında diğer proteinler ile bir araya gelerek inaktive olması, gastrointestinal sistem ve kanda proteazlar ile parçalanması, böbrek ve karaciğerlerden hızlı klirensi, yüksek toksisite ve immünojenite, düşük oral absorbsiyon, düşük metabolik stabilite, yüksek üretim maliyetleri gibi sebepler nedeni ile in vivo uygulamaların tamamen gerçekleşememekte ve sadece çok az bir kısmı klinik uygulamalara geçebilmektedir (Makowski vd., 2019).…”
Section: Introductionunclassified
“…Bu rekombinant sistemler arasında, mikroorganizma konakçıları genellikle en çok kullanılanlardır, çünkü bunlar yüksek düzeyde sentez, modifikasyon ve heterolog AMP'lerin salgılanmasını sağlayan özelliklere sahiptir. Bu konaklar tarafından üretilen AMP'ler de dahil olmak üzere piyasada halihazırda çeşitli rekombinant proteinler mevcuttur (Chaudhary vd., 2023). E. coli bakterisi, genetik ve biyolojik süreçleri iyi bilindiğinden, hızlı büyüme oranı, yüksek verim ve basit akış yukarı süreci sergilediği için en yaygın kullanılan mikrobiyal hücre fabrikasıdır (Carreón-Rodríguez vd., 2023).…”
Section: Introductionunclassified
See 1 more Smart Citation